Overview of Quality of Life in Children with Meningitis Post-Treatment - Vemila Apri Yoza (Indonesian Journal of Global Health Research, 2026)
The research, conducted from August 2020 to January 2021, was motivated by an indication of the quality of life problems of children with meningitis with prolonged treatment at dr. M. Djamil Padang related to the identification of complex neuropsychological sequelae in children. On the other hand, there has been an increasing trend in the number of pediatric meningitis patients hospitalized in these hospitals in recent years, especially the 2017–2019 period. The main objective of the study was to identify quality of life of children with meningitis post-treatment at dr. M. Djamil Padang in 2017–2019. The research method used was quantitative descriptive with a cross-sectional approach. Sampling in this study used purposive sampling, which found 34 respondents. The results showed that more than half (52.9%) of the sample of children with post-treatment meningitis had a poor quality of life, 29.4% had a poor quality of life with physical dimensions, 58.8% had a poor quality of life, respectively for the emotional and social dimensions, and 41.7% had a poor quality of life in the environmental/school dimension. In terms of age groups, poor quality of life was identified in 57.1% of children aged 2–4 years, 66.7% of children aged 5–7 years, and 40% of children aged 8–12 years.